HO-1 Modulates Aerobic Glycolysis through LDH in Prostate Cancer Cells - Florencia Cascardo; Nicolás Anselmino; Alejandra Páez; Estefanía Labanca; Pablo Sanchis; Valeria Antico-Arciuch; Nora Navone; Geraldine Gueron; Elba Vázquez; Javier Cotignola (MDPI AG, 2021)
Prostate cancer (PCa) is the second most diagnosed malignancy and the fifth leading cause of cancer associated death in men worldwide. Dysregulation of cellular energetics has become a hallmark of cancer, evidenced by numerous connections between signaling pathways that include oncoproteins and key metabolic enzymes. We previously showed that heme oxygenase 1 (HO-1), a cellular homeostatic regulator counteracting oxidative and inflammatory damage, exhibits anti-tumoral activity in PCa cells, inhibiting cell proliferation, migration, tumor growth and angiogenesis. The aim of this study was to assess the role of HO-1 on the metabolic signature of PCa. After HO-1 pharmacological induction with hemin, PC3 and C4-2B cells exhibited a significantly impaired cellular metabolic rate, reflected by glucose uptake, ATP production, lactate dehydrogenase (LDH) activity and extracellular lactate levels. Further, we undertook a bioinformatics approach to assess the clinical significance of LDHA, LDHB and HMOX1 in PCa, identifying that high LDHA or low LDHB expression was associated with reduced relapse free survival (RFS). Interestingly, the shortest RFS was observed for PCa patients with low HMOX1 and high LDHA, while an improved prognosis was observed for those with high HMOX1 and LDHB. Thus, HO-1 induction causes a shift in the cellular metabolic profile of PCa, leading to a less aggressive phenotype of the disease.